Bahasa Satire dalam Meme Media Sosial - Ayu Suciartini, Ni Nyoman (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2020)
The satire style was chosen to express satire and criticism explicitly. In the style of communicating on social media, satire is also used in making memes. The problem with this research is how is satire language in meme culture on social media? The focus of this research is to reveal how political satire is discussed in memes on social media. The purpose of this study is to examine more deeply how the satire discourse is contained in pictorial texts or purely texts in social media memes. This research is interesting because the satire humor style contained in memes becomes an effective, absurd political, economic, educational, cultural, and other response that is able to shift, eliminate, then reverse and bring up new discourses. This study uses a critical discourse analysis by Norman Fairclough which has an identification that the discourse can be a series of verbal and written words or a series of speech acts. With this knife of analysis, it was found that satire in memes on social media is used in the form of satire and criticism of things that are being viral and how these issues affect social media to the real world. Memes are not seen as silent, passive, and finished texts as they are produced. Memes, on the other hand, are dynamic and moving strategies, through comedy-satire.